Language Training of Customs Affairs Specialists: International and Russian Experience - D. G. Korovyakovsky; T. Yu. Igumentseva; V. V. Volkova (Высшее образование в России)
The article presents the results of a study of the language training of specialists in the field of Customs affairs in Russia and several of foreign countries. The described international experience in the language training of customs affairs specialists in Australia, vietnam, Germany, China, Moldova, the United States of America allows to indicate its specificity, namely, a bias towards the development of bilingual competence, since a multicultural customs space requires a specialist to have the ability to conduct a dialogue, to know the cultural realities of a native and foreign language, to be able to realize this knowledge in direct communication with international partners.Russian experience of the language training of customs specialists is characterized, on the one hand, by the lack of regionalization and filling in the content of a foreign language on the basis of interdisciplinary integration with the content of the professional cycle disciplines, and on the other, by the widespread use of active teaching methods, information and communication technologies in teaching a foreign language, which positively affects the formation of readiness for professional intercultural communication.The authors conclude that a deeper study of the international experience of language training on the basis of comparative analysis is necessary in order to improve Russian training of a qualified customs specialist who is able to conduct effective professional activities in a foreign language environment.